The ABA-induced soybean ERF transcription factor gene GmERF75 plays a role in enhancing osmotic stress tolerance in Arabidopsis and soybean - Zhao, Meng-Jie (BMC Plant Biol, 2019)
BACKGROUND: Ethylene-responsive factors (ERFs) play important roles in plant growth and development and the response to adverse environmental factors, including abiotic and biotic stresses. RESULTS: In the present study, we identified 160 soybean ERF genes distributed across 20 chromosomes that could be clustered into eight groups based on phylogenetic relationships. A highly ABA-responsive ERF gene, GmERF75, belonging to Group VII was further characterized. Subcellular localization analysis showed that the GmERF75 protein is localized in the nucleus, and qRT-PCR results showed that GmERF75 is responsive to multiple abiotic stresses and exogenous hormones. GmERF75-overexpressing Arabidopsis lines showed higher chlorophyll content compared to WT and mutants under osmotic stress. Two independent Arabidopsis mutations of AtERF71, a gene homologous to GmERF75, displayed shorter hypocotyls, and overexpression of GmERF75 in these mutants could rescue the short hypocotyl phenotypes. Overexpressing GmERF75 in soybean hairy roots improved root growth under exogenous ABA and salt stress. CONCLUSIONS: These results suggested that GmERF75 is an important plant transcription factor that plays a critical role in enhancing osmotic tolerance in both Arabidopsis and soybean.